Strategi Double Skin Fasade pada Bangunan Kampus National Central University dalam Menurunkan Kebutuhan Energi Pendinginan - Dewi, Cynthia Permata; Huang, Rong -Yau; Nugroho, Agung Murti (RUAS, 2013)
Building façade plays significant role in building energy efficiency and sustainability. Double Skin Façade (DSF) strategy comes as one of solution in advance building façade design technology. The aim of this study is to observe the performance of DSF configuration (air gap width) and materials in terms of reducing cooling energy for energy efficiency in case study buildings in hot humid climate in Taiwan. DesignBuilder- EnergyPlus was used as simulation tool in this study. Two scenario based on the placement of DSF strategy were conducted. The results show that combination of 1.2m air gap and double glazed Low E could reduce the cooling energy demand up to 31.28%. This study proved that DSF strategy is possible to be applied on hot humid climate such as Taiwan.